Maternal depression and children's behavioral self-regulation: the role of parenting and children's screen time - Wang, Shuang (Springer Nature, 2024)
Family processes such as maternal parenting and family screen exposure are significantly related to children's gains in behavioral self-regulation, but the potential mechanism of these relations remains unknown. In this study, we investigated how maternal depression is associated with children's behavioral self-regulation through the mediating role of maternal supportive parenting and children's family screen time. A total sample of 657 Chinese children and their mothers was recruited. Results from structural equation models indicated that supportive parenting and screen time partially mediated the effect of maternal depression on children's behavioral self-regulation by the sequential, after controlling for child demographic variables. Furthermore, supportive parenting played a partially mediating role in associations between maternal depression and children's self-regulation. The findings provide insights into parenting practices for early childhood development in the Chinese family environment.